Book Review – Appropriate Illustrations for Appropriate Functions: The Taxonomy of Illustration - Moris, Zailan (Penerbit Universiti Sains Malaysia (USM Press), 2013)
"A picture is worth a thousand words" is an eloquent statement of the critical role visual representation performs in communicating information. Whether it be in print or non-printed form such as the computer screen, a visual representation can communicate an idea or a concept or a body of information in a way which is more effective, economical and elegant than a wordy account of it. The effective use of a visual representation is dependent on both the type of representation that is used and how it is used in relation to the text that accompanies it, as well as the intended target audience. This subject is precisely the focal concern of Appropriate Illustrations for Appropriate Functions: The Taxonomy of Illustration written by Normahdiah Sheik Said, an academic at the Faculty of Modern Languages and Communication at Universiti Putra Malaysia, Serdang, Malaysia